Culex torrentium Mosquito Role as Major Enzootic Vector Defined by Rate of Sindbis Virus Infection, Sweden, 2009 - Jenny C. Hesson; Jenny Verner-Carlsson; Anders Larsson; Raija Ahmed; Åke Lundkvist; Jan O. Lundström (Emerging Infectious Diseases, 2015)
We isolated Sindbis virus (SINV) from the enzootic mosquito vectors Culex torrentium, Cx. pipiens, and Culiseta morsitans collected in an area of Sweden where SINV disease is endemic. The infection rate in Cx. torrentium mosquitoes was exceptionally high (36 infections/1,000 mosquitoes), defining Cx. torrentium as the main enzootic vector of SINV in Scandinavia.